Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China - Wu, Tie-Jun; Yang, Jian (Zootaxa, 2019)
Sinibotia lani, a new botiid loach is described from the Zuojiang River, located in Guangxi Autonomous Region, China. The species differs from other members of Sinibotia by a combination of the following morphological characters: body depth 17.5–21.1% SL; snout length shorter than postorbital length of head; eye diameter 10.2–13.2% HL; interorbital width 16.0–18.6% HL; suborbital spine reaching or extending beyond postorbital margin of eye; lower lip with pair of fleshy button-like clusters of papillae; dorsal-fin origin opposite to pelvic-fin origin, pelvic fin not reaching anus; includes six dark vertical bars on the body. A key to the species of Sinibotia is provided.